Sibling Relationships, Personality Traits, Emotional, and Behavioral Difficulties in Autism Spectrum Disorders. (25th November 2019) - Longobardi, C.; Prino, L. E.; Gastaldi, F. G. M.; Jungert, T.
Abstract : This study focused on parents' perceptions of the quality of sibling relationship and its association with some behavioral and emotional characteristics of the typically developing sibling. The participants were parents of children with autism spectrum disorder and typically developing siblings. The sample size was 43. The group comprised 14 fathers (32.6%) and 29 mothers (67.4%) aged 33–53 years (M = 43.56 ; SD = 5.23). The parents completed measures of siblings' emotional and behavioral difficulties, siblings' personality, and sibling relationships and their impact on families and siblings. The results showed that behavioral difficulties such as emotional symptoms, conduct problems, hyperactivity/inattention, and peer relationship problems were significantly associated with negative sibling relationships—characterized by rivalry, aggression, avoidance, and teaching behavior toward the brother or sister with an autism spectrum disorder. The implications are that sibling-focused interventions should focus on improving negative sibling relationships to reduce the impact on the difficulties of the typical development of the sibling of both genders and shape the content and delivery framework accordingly. This can be done by providing skills and approaches for enhancing sibling relationships so both parties benefit.